From intra- to inter-molecular hydrogen bonds with the surroundings: steady-state and time-resolved behaviours. Issue 7 (11th June 2015) - Alarcos, Noemí; Gutiérrez, Mario; Liras, Marta; Sánchez, Félix; Douhal, Abderrazzak
Abstract : The proposed photodynamic mechanisms for 6A-HBO at the femtosecond-picosecond scale in a DMF solution. Abstract : We report on the photodynamics of 2-(2′-hydroxyphenyl)benzoxazole (HBO), compared to its amino derivatives, 6-amino-2-(2′-hydroxypheny)benzoxazole (6A-HBO) and 5-amino-2-(2′-hydroxypheny)benzoxazole (5A-HBO) in N, N -dimethylformamide (DMF) solutions. HBO at S0 shows a reversible deprotonation reaction leading to the production of anionic forms. However, for 6A-HBO and 5A-HBO, DMF containing KOH is necessary to produce the anions. Excited HBO in DMF exhibits intra- as well as inter-molecular proton transfer (ESIPT and ESPT) reactions. With excitation at 330 nm, we observed the open-enol, anti -enol and keto forms with different emission and lifetimes (620 ps, 1.5 ns, and 74 ps, respectively), while with the excitation at 433 nm, only the anionic species emission was detected (3.7 ns). Contrary to HBO, 6A-HBO and 5A-HBO do not exhibit any proton transfer process, and only the emissions of the open-enol charge-transferred forms (open-ECT) were observed, which are comparable to those of their methylated derivatives (6A-MBO and 5A-MBO). Femtosecond studies of 6A-MBO and 6A-HBO in DMF indicate that an intramolecular charge-transfer (ICT) reaction (∼80 fs) and solvent relaxation process (2 ps) take place at S1 . Remarkably, the photoinduced breaking of the intramolecular hydrogen bond of 6A-HBO and the formation of an intermolecular hydrogen bond with DMF molecules occurs in 80 ps, while for 5A-HBO, this process occurs in less than 10 ps. In this study, we have demonstrated that the presence and position of the amino group in the HBO framework change both the S0 and S1 behaviours of the intramolecular H-bonds; a result which might be useful for the design and better understanding of supramolecular systems based on intra- and intermolecular H-bonds.